Currency and Its Evolution in the Conditions of Digital Transformation - H. N. Kostyukova (Цифровая трансформация, 2023)
The article discusses the evolution of the currency in the context of digital transformation. The main forms of fiat money are presented, including their modern development through digital form, as well as distinctive features. Attention is paid to the essence and features of the use of electronic money, their main differences. The focus is on the digital currency of the central bank. Information on the introduction and use of digital currency of central banks has been accumulated and systematized. The relevance of the introduction of the digital currency of the central bank is determined, its differences from the cryptocurrency are listed. The essence of the blockchain is explained and the process of its functioning is considered. The main models for the functioning of the digital currency of central banks, as well as options for cross-border settlements through the use of the digital currency of central banks, are indicated. The prospects for the integration of digital currencies of central banks are touched upon, including their impact on cross-border settlements.